COL1A1-PDGFB fusion uterine fibrosarcoma: A case report with treatment implication - Samuel L. Grindstaff; Jessica DiSilvestro; Katrine Hansen; Paul DiSilvestro; C. James Sung; M. Ruhul Quddus (Elsevier, 2020)
COL1A1-PDGFB gene fusion associated uterine sarcoma, so called dermatofibrosarcoma-like tumor, a recently reported entity in the uterine corpus, morphologically appears as high grade sarcoma with some features of dermatofibrosarcoma. So far only one other case has been reported in the uterine corpus and two in the uterine cervix. Identification of this gene fusion allows greater choice of targeted therapy in these patients. All the reported cases in the mullerian system are found to be CD34 positive by immunohistochemistry, a commonly used antibody in most immunohistochemistry laboratories. We would, therefore, propose routine CD34 immunohistochemical staining in all high grade uterine sarcomas which have failed other common immunohistochemical markers. Keywords: Uterine sarcoma, Dermatofibrosarcoma protuberans (DFSP), COL1A1-PDGFB fusion, Imatinib